A quasi‐experimental trial of the clinical and economic impact of implementing of hepatitis B immunoglobulin policy post needle stick and sharp injuries in reducing its unnecessary use at a tertiary care hospital. Issue 10 (29th June 2021) - Alshehail, Bashayer; Alotaibi, Nouf; Joseph, Royes; Alshayban, Dhafer
SUMMARY: Introduction: Hepatitis B virus infection has the highest rate of transmission out of the blood‐borne viruses in health care workers. Exposure to HBsAg positive source should be managed based on Hepatitis B serology results. Given that Hepatitis B immunoglobulin (HBIG) is an expensive medication with limited stock levels, it should be given more attention to make sure of its optimum use. This trial aims to evaluate the effectiveness of a policy on the use of HBIG following needle stick and sharp injuries among health care workers. Methods: It is a quasi‐experimental trial conducted at a Tertiary Care hospital in Saudi Arabia. The participants were health care workers who received HBIG following needle stick and sharp injuries from January 2018 to May 2020. Before and after implementing departmental guidelines and education on the post‐exposure procedure, the trial re‐evaluated the need for HBIG among the receivers. Results: A total of 60 health care workers received HBIG for needle stick and sharp injuries between the trial period (pre‐ and post‐implementation). The percentage of patients who received inappropriate HBIG was significantly lower during the post‐implementation of the guideline (30%) than that among the pre‐implementation period (60%). Thus, the direct cost associated with the inappropriate use was reduced from SAR 30000 to SAR 13500 post‐implementation. Conclusion: The implementation of HBIG guidelines of use and education has led to a statistically significant decrease in its inappropriate use and led to cost reduction.